Navigating the Moral World: Contrasting Adolescents’ Moral Dilemmas in Social Media and Real-life Environments - Rakinić, Kristina (ETHICS IN PROGRESS, 2024)
Moral dilemmas arise at the intersection of one's core moral beliefs. This descriptive qualitative study delves into the complex moral world of adolescents to examine and draw parallels between the context, conflict and content of their moral dilemmas in real life and social media environments. A purposive sampling method was employed with a total of 130 Slovenian adolescents (average age of 17.3 years). The data was analyzed using a deductive and inductive approach. Commonalities of moral dilemmas emerged in the context (largely involving friends) and content (primarily rooted in the care/harm foundation). However, when the conflicts were analysed, remarkable differences emerged, shaped by the unique dynamics of social media. As the realm of morality on social media remains largely unexplored from an adolescent perspective, our findings offer a novel perspective on this complex issue. Our study can also open the way for more effective moral education in the context of social media.